Insights into Watson–Crick/Hoogsteen breathing dynamics and damage repair from the solution structure and dynamic ensemble of DNA duplexes containing m1A. Issue 9 (21st March 2017) - Sathyamoorthy, Bharathwaj; Shi, Honglue; Zhou, Huiqing; Xue, Yi; Rangadurai, Atul; Merriman, Dawn K.; Al-Hashimi, Hashim M.
Abstract: In the canonical DNA double helix, Watson–Crick (WC) base pairs (bps) exist in dynamic equilibrium with sparsely populated (∼0.02–0.4%) and short-lived (lifetimes ∼0.2–2.5 ms) Hoogsteen (HG) bps. To gain insights into transient HG bps, we used solution-state nuclear magnetic resonance spectroscopy, including measurements of residual dipolar couplings and molecular dynamics simulations, to examine how a single HG bp trapped using the N 1-methylated adenine (m 1 A) lesion affects the structural and dynamic properties of two duplexes. The solution structure and dynamic ensembles of the duplexes reveals that in both cases, m 1 A forms a m 1 AT HG bp, which is accompanied by local and global structural and dynamic perturbations in the double helix. These include a bias toward the BI backbone conformation; sugar repuckering, major-groove directed kinking (∼9°); and local melting of neighboring WC bps. These results provide atomic insights into WC/HG breathing dynamics in unmodified DNA duplexes as well as identify structural and dynamic signatures that could play roles in m 1 A recognition and repair.